The Process of English Internationalization in the Ukrainian Educational Paradigm - Leleka, Tetiana; Ivanenko, Nadiia; Demeshko, Inna; Kapitan, Tetiana; Demchenko, Inha (Slavistica Vilnensis, 2023)
The research is devoted to the study of the problem of English loanword adaptation in the Ukrainian youth slang as a result of innovative processes in the educational system caused by the flow of language globalization. The globalization of the English language as a result of the information revolution and of all human activity is an unprecedented phenomenon in the world language system that is altering widely held beliefs about literacy and foreign languages. The main hypothesis of the study is an increase in the number of borrowed words in the speech of the Ukrainian youth. The paper attempts to analyze the trends in the use of the loanwords that have Ukrainian one-word equivalents over 5 years, from 2016 to 2021. To obtain data on the use of loanwords, respondents aged 15–17 (school pupils), 18–20 (university students), and 21–23 (university graduates) have been interviewed. According to the problems mentioned, the article aims to describe the use of English loanwords in the Ukrainian language caused by language globalization. The study intends to explore whether Ukrainian speakers prefer to use English loanwords instead of the Ukrainian equivalents that are connected with the role of English in the educational system and whether gender is a significant factor in the use and further assimilation of English loanwords.
Keywords: English internationalization; language globalization; loanwords; assimilation; youth slang; educational system